Improvising a Way Out of Darkness - Nicholson Parker, Patricia (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Patricia Nicholson Parker is the founder and director of the New York-based non-profit arts organization Arts for Art. In this piece, she writes of the ways in which improvisation is central to her work as both an artist and an organizer. She sees improvisation as a strategy of resistance to the degradation of “the sacredness of Life itself.”